Intercellular adhesion molecule-1 protects against adipose tissue inflammation and insulin resistance but promotes liver disease activity in western-diet fed mice - Eswaran, Sreepradha; Gebert, Laura; Schraven, Sarah; Treichel, Nicole; Ritz, Thomas; Hamm, Sabine; Seeger, Agnes; Kiessling, Fabian; Clavel, Thomas; Dreschers, Stephan; Wagner, Norbert; Schippers, Angela (Scientific reports, 2025)
Metabolic dysfunction associated steatotic liver disease (MASLD) presents a growing global health problem. Disease progression is promoted not only by hepatic leukocyte accumulation but also by inflammatory signals from adipose tissue and an altered gut microbiome. To determine the contribution of intercellular adhesion molecule-1 (ICAM-1) to MASLD pathogenesis, male mice with an ICAM-1 mutation (Icam1tmBay) and wild type (WT) mice were compared in 12 and 24-week feeding experiments with a Western-style diet (WD) containing 40 kcal% fat, 20 kcal% fructose, and 2% cholesterol. WD-induced MASLD was accompanied by increased ICAM-1 expression in liver, epididymal white adipose tissue (EWAT), and intestine in WT mice. WD-fed Icam1tmBay mice exhibited increased circulating neutrophils, higher frequencies of inflammatory leukocytes in EWAT, and a worsened glucose tolerance when compared to WT mice. In contrast, the mutation resulted in reduced WD-induced liver disease activity and less accumulation of intrahepatic leukocytes. WD-feeding caused substantial changes in fecal microbiota with decreased microbial diversity that differed between the mouse strains. In conclusion, ICAM-1 positively regulates adipose tissue homeostasis and protects from insulin resistance but promotes liver damage in diet-induced obesity. This points to organ-specific roles for ICAM-1 and the potential of liver-specific targeting of ICAM-1 for treatment of MASLD.